The clouds in the sky - Fisher, Carol-Anne (My first reading books. Shapes and sizes)
The children go on a trip to the mountains with their two monitors Colin and Cathy. While. they are outdoors they learn how to identify the different. shapes and sizes of the things they see around them. The paths. are long and they bend, the sun is a big circle in the sky, their tents look like small triangles when they observe them from the mountain top and even the clouds have differrent shapes.